Dynamic restoration and crystallographic texture of a friction-stir processed Al–Mg–SiC surface nanocomposite. Issue 14 (22nd September 2018) - Khodabakhshi, F.; Nosko, M.; Gerlich, A. P.
ABSTRACT: In this study, SiC nanoparticles (∼50 nm, 3 vol%) are homogenously incorporated within an Al–Mg alloy metal matrix during multi-step friction-stir processing (FSP) to fabricate an Al-matrix surface nanocomposite. A fundamental understanding is developed, correlating microstructural features and crystallographic textural components in the context of the material flow pattern and operative dynamic restoration phenomena using electron backscattering diffraction and high resolution-transmission electron microscopy analysis. The annealed base metal does not contain any preferred orientation and its texture is completely random. Incorporation of SiC nanoparticles via FSP results in significant grain structural refinement down to the size of ∼1.4 µm and changing the textural component towards the Goss/Cubic and P1/P2 dominant fibre components in the centre of stirred zone.